Body sensor networking, design, and algorithms - Sanei, Saeid; Constantinides, A. G.; Jarchi, Delaram, 1983- (Hoboken, NJ : John Wiley & Sons, Inc., 2020)
"The book aims at providing a complete reading material for clinicians, engineers, mobile communication system developers, and researchers in the related fields and familiarizing them with the state of the art in theoretical and manufacturing developments of body sensors and e-health, the measurements, processing, recognition, and decision making together with their implementation. It also provides the advances in sensor networking and cooperative networks, noninvasive and implantable sensor microelectronics, and the related topics on optimisation, energy minimisation and harvesting, as well as quality of service. The content of this book is proposed based on the market need and the demands of researchers in the related field. This is expected to follow the table of content provided at the end of this proposal. Clinical aspects, sensor development and technology, sensor networking, data processing and recognition, mobile networking, and data mining will be well covered and included in this book"--
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Body area networks (Electronics); Body area networks (Electronics); Electronic books